Effects of an educational intervention in the return of women to receive the result of the examination of Papanicolaou. - Camila Teixeira Moreira Vasconcelos; Ana Karina Bezerra Pinheiro (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
One of the activities of the programme of control of cervical uterine cancer (CUC) is the education in health . Thus, any action to control the CCU without the participation of the educational component that reaches the population of women will be successful. The explanation on the examination of a more intensive facilitates a better understanding of the process nullifying the construction of negative reviews about it. The increase in the provision of services, in the prevention and treatment of cases of CUC will have its limited scope, if women do not return to get the results of the examination. This study aims to: assess the effects of an educational intervention on the Pap test, in relation to the rate of return of women to receive the results; check the knowledge, attitude and practice of women with respect to the examination of Papanicolaou and describe the process education for women who awaiting the completion of the examination of Papanicolaou based on the model of adult education proposed by Paulo Freire. This study will be experimental, the type randomized clinical trial, conducted in a Centre for Family Health (CFH) from Fortaleza-CE. The study population will be composed by women belonging to the area of that CESAF. Women participating in the study will be randomly selected for the control group and the intervention group. The data collection will be held in three stages for the group of intervention: investigation KAP (Knowledge, Attitude and Practice), educational intervention and consultation of return, and, in two steps for the control group: CAP investigation and consultation of return.